新しい気球分離型無人航空機大気観測システム開発と昭和基地上空夏季自由対流圏のエアロゾル時空間変動 - 東野, 伸一郎; ヒガシノ, シンイチロウ; 林, 政彦; ハヤシ, マサヒコ; 梅本, 紫衣奈; ウメモト, シイナ; 長崎, 秀司; ナガサキ, シュウジ; 西村, 大貴; ニシムラ, モトキ; 尾塚, 馨一; オズカ, ケイイチ; et al. (国立極地研究所, 2021)
エアロゾルの数濃度鉛直分布観測やサンプリングにおいて，運用が手軽でありながら到達高度の高いゴム気球による観測方法と，自律飛行が可能な無人航空機（Unmanned Aerial Vehicle, UAV）の特徴を生かし，両者を組み合わせることによって，ゴム気球による観測では困難であった観測装置やサンプルの回収が可能となる新しいエアロゾル観測システムを開発した．本システムでは，UAV にエアロゾル数濃度観測装置およびサンプラを搭載し，気球に懸吊して上昇中に観測を行う．観測終了後に気球からUAV を分離し，自律滑空により放球地点までUAV が帰還することによって回収を行う．このシステムを用いて，第54 次日本南極地域観測隊の夏行動において5 回の観測フライトを行い，最高高度10 km までの観測と分離・回収に成功した．本研究で開発されたUAV システムによるエアロゾル粒径分布観測と，回収したエアロゾルサンプルの分析に基づき，2013 年1月の南極自由対流圏および成層圏底部には，中緯度の中規模火山噴火を起源とする硫酸を主成分としたエアロゾルが輸送されていた可能性が高いことが示された． A novel aerosol observation and sampling system has been developed by combining a rubber balloon and an unmanned aerial vehicle (UAV). The system takes advantage of the feature of an observation method using a rubber balloon, which is handy, inexpensive, and higher reachable observation altitude than those of other observation methods, and the feature of a UAV which can fly back to the released point autonomously. In this system, an optical particle counter, an aerosol sampler, and a GPS sonde are mounted on a motor-glider UAV. The UAV, which is suspended from a rubber balloon, is released from the ground. After finishing observation and sampling during its ascent, the UAV is recovered by separating from the balloon and gliding back to the released point autonomously. Five observation flights were performed successfully at Syowa Station in the summer activity of the 54th Japanese Antarctic Research Expedition, and the maximum observation and separation altitude reached 10 km. Number concentrations obtained by insitu measurements and morphology of recovered aerosols using the UAV show the possibility that the enhancement of sulfate aerosols in the free troposphere and bottom of the stratosphere were caused by the volcanic eruption in the mid-latitude in January 2013. departmental bulletin paper